2022
DOI: 10.47909/anis.978-9916-9760-0-5.98
|View full text |Cite
|
Sign up to set email alerts
|

D-Space, makerspace, and hackerspace in cyberspace: Cybersecurity strategies for digital preservation of library resources in the post-Covid-19 pandemic

Abstract: This paper explores the status of d-space in the milieu of makerspace and hackerspace in the cyber domain. These two belligerent sides excel in critical thinking, creativity, collaborations, and communication important for 21st-century skills a consequence of giving rise to difficulty in differentiating one side as an independent entity from the other. Organizations require one as a prerequisite for employment and application of the other in post-education. Covid-19 has consolidated these sides and brought wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…The thesis of (30) coincides with this study, who determined the influence of education for work on critical creative thinking in students, due to its results in (p < 0.05), since after manipulating the independent variable in the scheduled time, an achievement level of 67% was obtained. Likewise, (5) agrees with the research by having similar results applying the design thinking program at a high level 40.9%, medium level 59.1% and low level 0%, he insists that if there is no significance of all ways the program should be applied since the methodology is centered on the person. There was also a coincidence when comparing the results of (33) of the 30 students, 24 represent 80% on a scale always and 6 students represent 20% on a scale sometimes and never.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The thesis of (30) coincides with this study, who determined the influence of education for work on critical creative thinking in students, due to its results in (p < 0.05), since after manipulating the independent variable in the scheduled time, an achievement level of 67% was obtained. Likewise, (5) agrees with the research by having similar results applying the design thinking program at a high level 40.9%, medium level 59.1% and low level 0%, he insists that if there is no significance of all ways the program should be applied since the methodology is centered on the person. There was also a coincidence when comparing the results of (33) of the 30 students, 24 represent 80% on a scale always and 6 students represent 20% on a scale sometimes and never.…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, (34) was in an applied study who came to determine that the students of the mountains and the forests of Junín in ordinary basic education showed a creativity of 49.37% at the secondary level, so there is no characteristic high significant. In addition, (5) concluded that the theoretical bases reinforce the design thinking methodology, being relevant to develop creativity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, lifestyle in simple terms is a way of life used by individuals, groups and nations and is formed in a geographical, economic, political, cultural and religious context and this refers to the characteristics, behaviors and daily functions such as in their work environment, activities, fun and diet [3][4]; Although, with the use of ICTs there have been different positive and negative changes related to the health and well-being of the person, since ICTs influence the way of living and also how to adapt to situations in transformation. [5].…”
Section: Introductionmentioning
confidence: 99%
“…La creciente diversificación informacional demanda de las bibliotecas un servicio de calidad brindado por especialistas actos y capaces de atender las demandas del usuario, satisfaciendo con ello su carencia informacional. (12,13) De este modo, las bibliotecas universitarias como sistemas de información, tienen como principal objetivo servir de apoyo al estudio, la docencia y la investigación a través de la gestión, conservación y difusión de los fondos bibliográficos, audiovisuales y en otros soportes, facilitando el acceso a los mismos de manera que los usuarios satisfagan sus necesidades de información por medio de un servicio de calidad. (14,15) De las reflexiones anteriores, emerge la necesidad de enfatizar, que la calidad implica necesariamente juicios de valor y tiene como principio fundamental la mejora continua y es el resultado de la visión, la planificación, la aplicación disciplinada del trabajo y la habilidad en toda la institución.…”
Section: Introductionunclassified